ANALYSIS OF THE EFFECT OF PAYROLL SYSTEM AND PATIENT SAFETY CULTURE ON NURSE PERFORMANCE WITH JOB SATISFACTION AS THE INTERVENING VARIABLE IN INPATIENT ROOM PREMIER BINTARO HOSPITAL TANGERANG SELATAN - Rusdiana, Ima; Aida, Mus; Kusumapradja, Rokiah (LP2M IAI Al-Khairat Pamekasan, 2023)
This study is based on fluctuations in the risk of patients falling in the 2020 – 2021 period and the dynamics of performance problems in 2021 reflect problems regarding the performance of nurses in inpatient rooms in serving patients. The purpose of this study was to obtain evidence of the influence of the salary system and patient safety culture on the performance of nurses in inpatient rooms, with job satisfaction as an intervening variable. The research design used a cross sectional study, and made 135 nurses as the unit of analysis. The results of the study prove that the salary system and patient safety culture have a positive and significant direct effect on job satisfaction and performance, job satisfaction has a positive and significant direct effect on performance, and job satisfaction has a positive role in mediating the payroll system and patient safety culture on performance. By creating a sense of satisfaction for nurses with all aspects related to their work, they will be better able to present quality work results and achieve according to the standards set by the organization.